Financial stability of the federal budget and budgets of the Russian constituent entities subjects under Western sanctions - N. Z. Zotikov (Вестник университета)
According to the definition of the European Commission, public finances financial stability is the ability of a state to maintain current expenditures, conduct tax and social policy in the long term without the threat of loss of the country’s solvency to fulfill its obligations and stipulated expenditures. The subject of the study is the state of revenues and expenditures of the federal budget and budgets of the Russian constituent entities under the Western sanctions. The choice of the Ural Federal District regions (hereinafter – UFD) as the objects of the study is due to the significant share of oil and gas revenues in the federal budget revenues, the export-oriented regions place and role in the oil and gas revenues formation in the federal budget. The purpose of the study is to assess the budget system financial stability on the example of the federal budget and budgets of the Russian constituent entities, in particular, the UFD regions. The article uses generally accepted research methods, such as analysis and synthesis, generalization, grouping, tabular, etc. It has been established that the imposed sanctions have a negative impact on oil and gas revenues. Under such conditions, the budget system stability is supported by a low level of debt, especially at the federal level. The UFD export-oriented regions budget stability indicators exceed similar indicators of the Russian constituent entities budget. The budget stability risks remain the highest at the regional and local levels.